PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT (TQM), SISTEM PENGUKURAN KINERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL - Adam Marthin (2022)
This research is a quantitative research related to total quality management (TQM), performance measurement system, and organizational commitment and their influence on managerial performance. This study involved 39 managers from 27 shipping service company offices spread across Bekasi City as a sample. The sample selection in this study was carried out in a saturated manner. Hypothesis testing in this study uses path analysis by looking at the direct and indirect effects of each independent variable on the dependent variable using the SmartPLS tool, with a significance level of 5% (0.05). The results of the test obtained (1) there is insignificant effect on TQM on managerial performance, (2) there is insignificant effect on the performance measurement system on managerial performance, and (3) there is a positive and significant effect on organizational commitment to performance. managerial. Keywords: managerial performance, total quality management, performance measurement system, organizational commitment.